Interstitial Rural Youth: Contributions from a Somatic Rooting - Roa, María Luz (2023)
In this article we problematize the notion of roots from the perspectives of young people in post-pandemic rural Argentina, focusing on the somatic and symbolic ways in which young people inhabit rural worlds. We wonder about the ways of inhabiting rural youth today, as well as the constitution of youth identities linked to symbols, aesthetics and rural corporalities. For this, we present a comparative analysis of two cases of young people who live in scattered rural areas of the northeast and Argentine Patagonia. We consider information from two qualitative investigations that combine the use of interviews, observations, and workshops with young people. The analysis is organized in three dimensions. In the first place, we characterize the future projects of young people and the carnal and digit-carnal youth displacements and spatialities between the countryside, the city and the town. Secondly, we wonder about the somatics of rooting and uprooting from a phenomenological perspective, contemplating emotive, practical, and performative ways of inhabiting the territories and the indigenous and mestizo selves. Based on these indications, we finally propose a definition of rural youth as interstitial youth.